The changing face of international radio - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Radio, the major communication medium in many ACP countries, is changing fast. Since 1990, there has been a massive surge in the number of rural radio stations, now totalling more than 400, according to a recent survey for CTA. Urban stations have...